Obtaining silicon carbide via chemical vapor, plasma-chemical and sublimation methods - Zhuravlov, А.Yu.; Hovanskiy, N.А.; Khizhnyak, D.A.; Shirokov, B.M.; Semenov, N.A.; Shijan, А.V.; Strigunovskiy, S.V.; Yevsiukov, A.I.; Shevtsov, A.B.; Nazarenko, E.A.; Pilipenko, N.N. (Вопросы атомной науки и техники, 2017)
In the present paper the results of studies on obtaining silicon carbide via chemical gas phase, plasma-chemical and sublimation methods are described. The thermodynamic analysis of chemical reactions of silicon carbide in the presence of hydrogen and without was provided. Was found that, without free hydrogen reaction of silicon carbide formation can’t proceed. Established depending on ratio between the various active components of the gas phase SiCl₄:C₇H₈, entering the reactor, morphology of SiC layer. Was shown that, with increasing temperature of the substrate deposition rate increases, reaching a maximum temperature about ~ 1800 K with a steep decreasing at higher temperatures ranges, which is typical of a homogeneous reaction. From source (NbTa)SiC, received via chemical CVD, obtained films of SiC with sublimation method. Представлены результаты исследований по получению карбида кремния химическим газофазным, плазмохимическим и сублимационным методами. Проведен термодинамический анализ химических реакций получения карбида кремния в присутствии водорода и без него. Установлено, что без свободного водорода реакция образования карбида кремния протекать не может. В зависимости от различного соотношения между активными компонентами газовой фазы SiCl₄:C₇H₈, поступающими в реактор, изучена морфология SiC-слоя. Исследована кинетика процесса осаждения SiC. Показано, что с увеличением температуры подложки скорость осаждения возрастает, достигая максимума при температуре ~ 1800 K с резким снижением в области более высоких температур, что характерно для гомогенной реакции. Из полученного химическим газофазным методом источника (NbTa)SiC сублимационным методом получены плёнки SiC. Представлено результати досліджень по отриманню карбіду кремнію хімічним газофазним, плазмохімічним і сублімаційним методами. Проведено термодинамічний аналіз хімічних реакцій отримання карбіду кремнію в присутності водню і без нього. Встановлено, що без вільного водню реакція утворення карбіду кремнію протікати не може. Залежно від різного співвідношення між активними компонентами газової фази SiCl₄:C₇H₈, які надходять в реактор, вивчена морфологія SiC-шару. Досліджено кінетику процесу осадження SiC. Показано, що зі збільшенням температури підкладки швидкість осадження зростає, досягаючи максимуму при температурі ~ 1800 K з різким зниженням в області більш високих температур, що характерно для гомогенної реакції. З отриманого хімічним газофазним методом джерела (NbTa)SiC сублімаційним методом отримано плівки SiC.